More Wishing chair stories - Blyton, Enid (london Egmont, 2008)
Mollie and Peter and Chinky the pixie have more amazing adventures on their Wishing-Chair. They find gold at the end of the rainbow, they meet brownies and they visit the Land of Wishes. Best of all they get to help Santa Claus deliver presents for Christmas!You can be whisked away by Enid Blyton's magical Wishing-Chair stories